2023
DOI: 10.3390/toxics11040303
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Maternal and Fetal Toxicity Risks for Metronidazole-Related Teratogenicity and Hepatotoxicity through an Assessment in Albino Rats

Abstract: Metronidazole is the primary antimicrobial drug for treating acute and chronic vaginal pathogens during pregnancy; however, there has been insufficient research on placental disorders, early pregnancy loss, and preterm birth. Here, the potential activity of metronidazole on pregnancy outcomes was investigated. 130 mg/kg body weight of metronidazole was orally given individually to pregnant rats on gestation days 0–7, 7–14, and 0–20. Pregnancy outcome evaluations were carried out on gestation day 20. It was dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The most widely used and most effective clinical treatment for trichomoniasis is the drug metronidazole. However, the gradual increase of strains of Trichomonas vaginalis resistant to this drug, as well as issues such as mutagenicity in bacteria, carcinogenicity in mice, the ability to cross the placenta, and the possibility of teratogenicity in the fetus, do not present metronidazole as a suitable drug for trichomoniasis [ 2 , 3 ]. Some researchers have suggested that DNA vaccines or recombinant antigens can effectively stimulate immune responses against parasitic protozoa.…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used and most effective clinical treatment for trichomoniasis is the drug metronidazole. However, the gradual increase of strains of Trichomonas vaginalis resistant to this drug, as well as issues such as mutagenicity in bacteria, carcinogenicity in mice, the ability to cross the placenta, and the possibility of teratogenicity in the fetus, do not present metronidazole as a suitable drug for trichomoniasis [ 2 , 3 ]. Some researchers have suggested that DNA vaccines or recombinant antigens can effectively stimulate immune responses against parasitic protozoa.…”
Section: Introductionmentioning
confidence: 99%
“…The global use of prescribed and non-prescribed antibiotics is rising, provoking significant safety concerns. Neurological side effects associated with antibiotics are likely underdiagnosed and necessitate increased awareness and attention [ 1 ]. Metronidazole (MET) is a widely used antimicrobial drug due to its effectiveness against various bacteria and yeasts [ 2 ].…”
Section: Introductionmentioning
confidence: 99%